Effects of the Surgical Ligation of the Ureter in Different Locations on the Kidney over Time in the Rat Model - Abdolreza Mohammadi; Leila Zareian Baghdadabad; Parisa Zahmatkesh; Hedieh Moradi Tabriz; Alireza Khajavi; Gholamreza Mesbah; Parsa Nikoofar; Seyed Mohammad Kazem Aghamir (Advances in Urology)
Purpose. To evaluate the effects of the surgical ligation of the ureter in different locations on the kidney over time in the rat model. Methods. A total of 155 rats were enrolled and randomly divided into the case (n = 150) and control (n = 5) groups. The case group included three separate groups (fifty rats in each group) that underwent surgical ureteral ligation at the proximal, middle, and distal ureter. The laboratory tests, and tumor necrosis factor α (TNF-α), were measured in groups. The pathological evaluation for glomerular changes, tubular dilation, interstitial fibrosis, and interstitial infiltration of the inflammatory cells following the obstruction was performed (severity of tubular atrophy categorized too mild (+), moderate (++), and severe (+++)). To compare the continuous variables between the groups and between the measurement times, the analysis of variance (ANOVA) was used. Results. Our results revealed that the creatinine four weeks after the obstruction was significantly higher in the proximal group obstruction (p value: 0.046). The three groups had no significant differences regarding urine creatinine, serum sodium, and serum TNF (p value: 0.261). Obstruction did not change the glomerular morphology in three intervention groups after six weeks. The commencing of severe tubular atrophy in proximal, middle, and distal ureteral obstruction was at weeks three, four, and six, respectively. Conclusion. The location of ureteral obstruction is also crucial in deciding to intervene to relieve the complete ureteral obstruction. Severe tubular damage occurs in weeks three, four, and six in proximal, middle, and distal ureteral obstruction, respectively.